Kajian Geomorfologi Daerah Danau Ranau dan Sekitarnya - Rahmadini, Sesaria; Sutriyono, Edy; Ibrahim, Mochammad Malik (Mataram University, 2026)
The Ranau Lake area and its surroundings are located along the Bukit Barisan Range, which constitutes an active volcanotectonic zone influenced by the Sumatran Fault System. This study was conducted to identify geomorphic units and to understand the geomorphological processes that contribute to the formation of the landscape in the study area. The analysis was carried out using morphographic, morphometric, and morphogenetic approaches by utilizing Digital Elevation Model (DEM) data, topographic maps, and field observations. The results indicate that the geomorphology of the Ranau Lake area is composed of volcanotectonic, denudational, and volcanic landforms, which have developed through the interaction of tectonic activity, erosional processes, and Quaternary volcanism. In general, the regional morphology is characterized by steep relief, variable slope gradients, and radial to dendritic drainage patterns influenced by geological structures and lithological conditions. This geomorphological study is expected to provide insights into the landscape evolution of the Ranau Lake area and serve as a basis for regional geological analysis and land-use planning.